Hierarchical nanoflower arrays of Co9S8-Ni3S2 on nickel foam: a highly efficient binder-free electrocatalyst for overall water splitting - Illathvalappil, Rajith; Walko, Priyanka S.; Kanheerampockil, Fayis; Bhat, Suresh K.; Devi, R. Nandini; Kurungot, Sreekumar (Chemistry-A European Journal, 2020)
Hydrogen production is vital for meeting future energy demands and managing environmental sustainability. Electrolysis of water is considered as the suitable method for H-2 generation in a carbon-free pathway. Herein, the synthesis of highly efficient Co9S8-Ni3S2 based hierarchical nanoflower arrays on nickel foam (NF) is explored through the one-pot hydrothermal method (Co9S8-Ni3S2/NF) for overall water splitting applications. The nanoflower arrays are self-supported on the NF without any binder, possessing the required porosity and structural characteristics. The obtained Co9S8-Ni3S2/NF displays high hydrogen evolution reaction (HER), as well as oxygen evolution reaction (OER), activities in 1 m KOH solution. The overpotentials exhibited by this system at 25 mA cm(-2) are nearly 277 and 102 mV for HER and OER, respectively, in 1 m KOH solution. Subsequently, the overall water splitting was performed in 1 m KOH solution by employing Co9S8-Ni3S2/NF as both the anode and cathode, where the system required only 1.49, 1.60, and 1.69 V to deliver the current densities of 10, 25, and 50 mA cm(-2), respectively. Comparison of the activity of Co9S8-Ni3S2/NF with the state-of-the-art Pt/C and RuO2 coated on NF displays an enhanced performance for Co9S8-Ni3S2/NF both in the half-cell as well as in the full cell, emphasizing the significance of the present work. The post analysis of the material after water electrolysis confirms that the surface Co(OH)(2) formed during the course of the reaction serves as the favorable active sites. Overall, the activity modulation achieved in the present case is attributed to the presence of the open-pore morphology of the as formed nanoflowers of Co9S8-Ni3S2 on NF and the simultaneous presence of the surface Co(OH)(2) along with the highly conducting Co9S8-Ni3S2 core, which facilitates the adsorption of the reactants and subsequently its conversion into the gaseous products during water electrolysis.
Keywords: cobalt sulfide; electrocatalysts; Hydrogen evolution; overall water splitting; oxygen evolution

Hydrogen evolution via photocatalytic reforming of biomass with palladium nanoparticles decorated g-C3N4 nanosheets - Thara, Chinnu R.; Walko, Priyanka S.; Mathew, Beena (Renewable Energy, 2024)
Fossil fuel depletion and environmental toxins have made photocatalytic H2 production of paramount significance. A novel and unique technique for producing sustainable H2 and valorizing biomass using infinite solar energy is biomass photoreformation. Nevertheless, this environmentally friendly method is usually linked to severe reaction circumstances, insufficient selectivity, and restricted biomass conversion. Here, we present a novel one-pot photoreformation technique over porous g-C3N4 nanosheets surface-modified with Pd nano- particles to convert D-glucose to H2. By stacking the g-C3N4 photocatalyst into a 2D nanosheet structure, some of its inherent drawbacks can be mitigated. Furthermore, the inclusion of noble metal nanoparticles in these g-C3N4 nanosheet structures could significantly boost existing photocatalytic activity. The majority of solar radiation is composed of visible light, which makes up 45% of it, and ultraviolet light, which makes up 5%. Therefore, our focus has been on utilizing abundant visible light to facilitate biomass reformation. After 4 h of continuous irradiation, our composite photocatalyst exhibited exceptional visible light activity; its H2 evolution was 1839.84 mu molg- 1h- 1 , or about 27 times higher than that of undoped g-C3N4 nanosheets. The effectiveness of three different Pd loadings on g-C3N4 nanosheets for glucose reforming was examined. In the quest for an improved H2 evolution visible light active photocatalyst, g-C3N4 nanosheets made at various pyrolysis temperatures loaded with optimized Pd weight percentage were also examined.
Keywords: Biomass; D -glucose; g-C 3 N 4 nanosheets; Hydrogen evolution; palladium nanoparticles; Photocatalytic reforming